2020
DOI: 10.1021/acsami.9b15859
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Ag-Sputtered Materials Inactivating Bacteria by Surface Contact without the Release of Ag Ions: End of a Long Controversy?

Abstract: The study provides new evidence for Ag-coated polyester (PES) mediating Escherichia coli inactivation by way of genetically engineered E. coli (without porins, from now denoted porinless bacteria). This allows the quantification of the bactericidal kinetics induced by the Ag surface without the intervention of Ag ions. Bacterial inactivation mediated by Ag-PES was seen to be completed within 60 min. The samples were prepared by high-power impulse magnetron sputtering (HiPIMS) at different sputter powers. In an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…A number of bacterial colonies showed un-conspicuous reduction when bacteria were treated by K 3 [Fe­(CN) 6 ] with different concentrations (1.0–1.6 mM) (Figure S7), indicating good biocompatibility and weak antibacterial activity of the etchant. Considering the broad-spectrum antibacterial activity of Ag + , we studied if there was any difference in antibacterial activity of AAS-NPs produced by addition of different etchant concentrations. When [Fe­(CN) 6 ] 3– concentration was higher than 1.4 mM, the produced AAS-NPs killed >99.99% of all three bacteria, including S.…”
Section: Resultsmentioning
confidence: 99%
“…A number of bacterial colonies showed un-conspicuous reduction when bacteria were treated by K 3 [Fe­(CN) 6 ] with different concentrations (1.0–1.6 mM) (Figure S7), indicating good biocompatibility and weak antibacterial activity of the etchant. Considering the broad-spectrum antibacterial activity of Ag + , we studied if there was any difference in antibacterial activity of AAS-NPs produced by addition of different etchant concentrations. When [Fe­(CN) 6 ] 3– concentration was higher than 1.4 mM, the produced AAS-NPs killed >99.99% of all three bacteria, including S.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial mechanism of AgNPs has been widely studied [ 35 , 36 , 37 ]. According to the deconvoluted Ag 3d spectrum results, the synthesized AgNPs were primarily present in a metallic state ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Ag + ions, which are converted from AgNPs in the physiological environment, deform cell membranes and interact with some proteins [ 1 ]. Rtimi et al [ 37 ] proposed a new perspective. They concluded that the interaction between Ag-sputtered materials and bacteria, through direct surface contact-induced redox reaction, resulted in an increase in the permeability of the bacterial cell envelope and the modification of the interfacial bacterial potential.…”
Section: Resultsmentioning
confidence: 99%
“…Ag reacts almost instantaneously with air (O 2 ) and atmospheric water vapor, leading to AgOH. Only 2-3 atomic layers of AgOH (0.4-0.6 nm thick) are found on NPs' surfaces [31] The Langmuir-Hinshelwood (L-H) kinetic model is frequently employed to describe bacterial inactivation kinetics [6,7]. This model is applied to process the data obtained during virus inactivation mediated by TiO 2 and metal-TiO 2 photocatalysts [5][6][7][8].…”
Section: Ifct Ag/tio 2 -Mediated Bacterial/virus Inactivationmentioning
confidence: 99%
“…Ag reacts almost instantaneously with air (O 2 ) and atmospheric water vapor, leading to AgOH. Only 2-3 atomic layers of AgOH (0.4-0.6 nm thick) are found on NPs' surfaces[31]. AgOH decomposes spontaneously to Ag 2 O.…”
mentioning
confidence: 99%